La folie amoureuse et la notion de « désordre sacré » dans deux romans, ukrainien et corse - Olena Berezovska Picciocchi (Multilinguales)
The goal of our study is to partially illustrate G. Devereux’s thesis according to which some psychiatric disorders are localized in what he has designated as “unconscious ethic”. To achieve this, we suggest to compare two literary prose works Тіні Забутих Предків [Les Ombres des ancêtres oubliés] (1911) by the Ukrainian writer Mykhaïlo Kotsioubynsky and Le Berger des morts – Mal’Concilio (1974) by Jean Claude Rogliano, a French expression Corsican writer. The anchoring of both stories in the cultural tradition of their respective communities the Hutsul and the Corsican, the type of their main characters, their marginal social position, their fatal love “madness”, allowed a reading of these two works in the light, of the notion of the “Sacred Disorder” of the ethno-psychiatry of Georges Devereux, (1908-1985).